An Ultra-Wideband Reference Frequency Chirp Generator Utilizing Fractional Frequency Divider With High Linearity - Bent Walther; Lukas Polzin; Marcel van Delden; Thomas Musch (IEEE Open Journal of Circuits and Systems)
Using physically separated multiple-input multiple-output (MIMO) systems for millimeter-wave measurement systems based on linear frequency chirps poses unique challenges for generating a modulated reference chirp to apply high coherence. The reference frequency chirp is crucial for the measurement accuracy of the overall system and should feature high bandwidth, low phase noise, and high linearity. For this reason, we present a novel architecture combining a fixed-integer phase-locked loop (PLL) with a fast-modulated frequency divider. Thus, modulated output frequencies of up to 2 GHz with an adjustable bandwidth of up to 1.75 GHz are achieved while maintaining low phase noise of −140 dBc/Hz at 1 MHz from the carrier at the center frequency. Synchronous programming and modulation of the fractional frequency divider is done by a new type of control utilizing fast transceivers in a field-programmable gate array (FPGA), which does not require back-synchronization to the frequency divider. Measurements with the novel reference frequency chirp generator combined with a V-band PLL reveal a low RMS linearity error of 0.67ppm of the reference chirp for a chirp duration of 1 ms and a bandwidth of 363 MHz.